A livre adesão nas sociedades cooperativas, considerando a impossibilidade técnica de prestação de serviços - Golin, Clicio Barbiero (Universidade do Vale do Rio dos Sinos, 2019)
The human being, as a social being, has cooperation as an inherent principle. However, cooperativism as it is known today arose on October 24, 1844 in the "toad cross" in England, with the record of "Rochdale's pioneering society", and the principle of free adhesion there originated. In Brazil, membership is free to cooperative societies, only being allowed a restriction when there is a technical impossibility in the provision of services. In addition, cooperativism, due to its social and economic relevance, has gained a prominent place in the whole globe. Cooperativism is treated with distinction by several international entities. In Brazil, cooperativism is present in various legal provisions, from constitutional or infra-constitutional norms. The restriction of free adhesion, when there is technical impossibility in the provision of cooperative services, can be challenged judicially, and this condition must be effectively demonstrated at the time of denial of membership. The demonstration of the technical impossibility by the cooperative must be given in a clear and objective way so that there is no doubt about this condition.
Keywords: Cooperativismo; Livre adesão; Impossibilidade técnica; Demonstração; Cooperativism; Free membership; Technical impossibility; Demonstration; ACCNPQ::Ciências Sociais Aplicadas::Direito